Studi Eksperimental Penggunaan Solar Collector dalam Pengeringan Ikan Menggunakan Media Pasir - Muhammad Fadil Al Rahman; Yolli Fernanda; Primawati Primawati; Andre Kurniawan (Unversitas Negeri Padang, 2025)
Fish drying using a solar collector with heat storage is hot air taken directly from solar energy channeled into the solar collector which can store heat energy from the sun with sand media in the solar collector. The research method involves drying fish at different temperature and time variations, and comparing the results with conventional drying methods. The parameters measured include the moisture content and the dried fish produced. In addition, the dried fish produced from this process had better texture and flavor, thus improving the quality of the final product. The purpose of this research is to dry fish using a solar collector by using solar energy media to absorb heat energy. The test results of the fish dryer using sand media showed the highest temperature on the inside of the oven with a temperature of 41 ° C at 11:00 WIB with a solar intensity of 499 W/m². Drying on fish occurs a reduction in fish content, namely 49.25% to 64.70% for 8 hours of drying using a solar collector. The drying rate of the fish drying process is 0.091 g/min to 0.061 g/min with a collector efficiency level of 15.04% on the first day of testing and 16.52% on the second day of testing. In the process of drying fish for two days, there is a reduction in fish mass from 67 grams to 12 grams with a mass reduction of about 55 grams.